Genome-wide DNA methylation of the liver reveals delayed effects of early-life exposure to 17-α-ethinylestradiol in the self-fertilizing mangrove rivulus. Issue 5 (4th May 2022) - Voisin, Anne-Sophie; Suarez Ulloa, Victoria; Stockwell, Peter; Chatterjee, Aniruddha; Silvestre, Frédéric
ABSTRACT: Organisms exposed to endocrine disruptors in early life can show altered phenotype later in adulthood. Although the mechanisms underlying these long-term effects remain poorly understood, an increasing body of evidence points towards the potential role of epigenetic processes. In the present study, we exposed hatchlings of an isogenic lineage of the self-fertilizing fish mangrove rivulus for 28 days to 4 and 120 ng/L of 17-α-ethinylestradiol. After a recovery period of 140 days, reduced representation bisulphite sequencing (RRBS) was performed on the liver in order to assess the hepatic genome-wide methylation landscape. Across all treatment comparisons, a total of 146 differentially methylated fragments (DMFs) were reported, mostly for the group exposed to 4 ng/L, suggesting a non-monotonic effect of EE2 exposure. Gene ontology analysis revealed networks involved in lipid metabolism, cellular processes, connective tissue function, molecular transport and inflammation. The highest effect was reported for nipped-B-like protein B (NIPBL) promoter region after exposure to 4 ng/L EE2 (+ 21.9%), suggesting that NIPBL could be an important regulator for long-term effects of EE2. Our results also suggest a significant role of DNA methylation in intergenic regions and potentially in transposable elements. These results support the ability of early exposure to endocrine disruptors of inducing epigenetic alterations during adulthood, providing plausible mechanistic explanations for long-term phenotypic alteration. Additionally, this work demonstrates the usefulness of isogenic lineages of the self-fertilizing mangrove rivulus to better understand the biological significance of long-term alterations of DNA methylation by diminishing the confounding factor of genetic variability.